Effect of Risk Management and Effectiveness of Its Implementation on Performance of Riau High Court - Naibaho, Ros Endang; Madya, Faizal; Yuliana, Ernik (Adpebi International Journal of Multidisciplinary Sciences, 2025)
Purpose – The purpose of the research is to determine the influence and relationship of risk management, the effectiveness of its application to improve performance in the Riau High Court by placing the effectiveness of the implementation of risk management as an intervening variable.Methodology/approach – This research is explanatory descriptive with a quantitative approach. The subject of this study is the risk owner of the Riau High Court. Sampling was done using the probability sampling method with proportionate stratified random sampling. The respondents totaled 56 respondents of the Riau High Court. Data collection was carried out with a closed-ended questionnaire with a likert scale. The analysis method used is Partial Least Square-Structural Equation Modeling (PLS SEM) with the help of SmartPLS software version4.Findings – This study found that the application of risk management has very strong effect size on the effectiveness of absorption and organization as well as performance. The effectiveness of the application as an intervener has a weak impact on performance, which. The results of the hypothesis test showed that effectiveness had positive relationship, but did not have a significant effect on performance improvement. The application of risk management has a positive and significant effect on the effectiveness of the implementation and. The application of risk management has positive and significant effect on improving the performance. An R2 analysis showed that risk management factors were able to explain 86% of the effectiveness factor. Meanwhile, risk management and effectiveness can explain the 90% performance improvement factor. This shows that there are still 14% of the effectiveness factors and 10% of the performance factors